Frontispiece: Tuning Phonon Energies in Lanthanide‐doped Potassium Lead Halide Nanocrystals for Enhanced Nonlinearity and Upconversion. Issue 1 (28th December 2022) - Zhang, Zhuolei; Skripka, Artiom; Dahl, Jakob C.; Dun, Chaochao; Urban, Jeffrey J.; Jaque, Daniel; Schuck, P. James; Cohen, Bruce E.; Chan, Emory M.
Abstract : Upconversion Nanoparticles . Phonon‐engineered, lanthanide‐doped upconverting nanoparticles with the lowest phonon energies available to date are reported by Emory M. Chan et al. in their Communication (e202212549 ).